2017
DOI: 10.1371/journal.pone.0173320
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic time warping assessment of high-resolution melt curves provides a robust metric for fungal identification

Abstract: Fungal infections are a global problem imposing considerable disease burden. One of the unmet needs in addressing these infections is rapid, sensitive diagnostics. A promising molecular diagnostic approach is high-resolution melt analysis (HRM). However, there has been little effort in leveraging HRM data for automated, objective identification of fungal species. The purpose of these studies was to assess the utility of distance methods developed for comparison of time series data to classify HRM curves as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Some recent microbiological applications that used this technology have been reported. Various studies in Switzerland (Landolt et al ), USA (Esteves et al ), Italy (Pugliese et al ), and China (Lu et al ) demonstrated the potential of HRM to differentiate between bacterial species rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…Some recent microbiological applications that used this technology have been reported. Various studies in Switzerland (Landolt et al ), USA (Esteves et al ), Italy (Pugliese et al ), and China (Lu et al ) demonstrated the potential of HRM to differentiate between bacterial species rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…The DTW method is one of the methods used for analyzing time series data [1,[6][7][8] and can be adapted for trajectory shape analysis, as was done in this study. This study was successful in demonstrating the effectiveness of using the DTW method for fragment shape analysis.…”
Section: Discussionmentioning
confidence: 99%
“…To measure the similarity among fragmented trajectories for detecting unique classes of motifs, the DTW method was adopted. The DTW method can measure the similarity between 2 temporal sequences of data, such as shapes, genetic and sound analysis data [7,8], and trajectory similarity. The advantage of the DTW method is that it can align two temporal sequences automatically, as each trajectory typically has different time stamps.…”
Section: Fragment Similarity and Cluster Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…DTW calculates the distance between reference data and test data which has never been trained, and the smallest distance indicates the greatest similarity [18][19][20]. And it holds the benefits of requiring small amount of fault reference data, no need of selecting feature vectors, and requiring limited historical data and a priori knowledge.…”
Section: Introductionmentioning
confidence: 99%